Interpretation of the Myth of the Giant Carp that Dwells in Lake Toba from Aldo Leopold's Perspective in Building Ecological Awareness - Krisma Natal Josepa Simbolon; I Wayan Marianta (Jurnal Pendidikan dan Kebudayaan Missio, 2024)
Pollution in the waters of Lake Toba is increasing. Serious efforts are needed to respond to it. Interpreting the myth about the giant carp that inhabits Lake Toba can be an effective tool to minimise the pollution. In Land Ethics, Aldo Leopold says that humans are members of a community whose parts are interdependent. From the perspective of Leopold's ecological ethics, the author tries to explore the meaning of the myth of the giant carp that inhabits Lake Toba in response to the environmental issues that are happening in Lake Toba, where this mythology developed. The methodology used is a literature study. The author found that the myth contains ecological values that can foster ecological awareness in society. This awareness is very necessary considering the state of the ecosystem in Lake Toba which has begun to be damaged. Lake Toba is a subject that has interests and rights to exist like humans. Humans need to be responsible and respectful towards Lake Toba. The sustainability of the Lake Toba ecosystem is in the hands of humans, especially the people who live around Lake Toba. Just as humans need nature to live, nature also needs to be nurtured and maintained by humans so that the balance of the lake ecosystem relationship is maintained. The interpretation of this myth is expected to help develop environmental ethics and can be realised in environmental restoration, especially around the Lake Toba area.